Analisis Nilai Karakter Disiplin Siswa melalui Ekstrakurikuler Cerita Bergambar (Cergam) di SD Negeri 4 Kampungdalem - Karista, Adinda; Ana, Ria Fajrin Rizqy (Jurnal Simki Postgraduate, 2024)
Extracurricular activities are able to foster disciplined character in students, however, based on pre-observation, it was found that many students arrived late during extracurricular picture story activities (cergam). The aim of this research is to analyze the disciplinary character values ​​possessed by students through learning at SD Negeri 4 Kampungdalem. This type of research is a qualitative phenomenological approach with 25 students as the subject. Data collection techniques use observation, interviews and documentation. Data analysis techniques use data collection, data reduction, data presentation, and conclusions and verification. Checking the validity of the data uses triangulation. The results of the research are an analysis of the discipline character of students through extracurricular cergam at SD Negeri 4 Kampungdalem which can be seen through 5 indicators, namely that students comply with the specified schedule, dress politely, have the awareness to return borrowed items, and are on time in completing assignments, while in cergam It can be seen through 3 indicators that students can sketch real shapes, draw with everyday life themes, give colors that match the real object, and draw living objects.